Experimental study on the mechanical properties of 7xxx aluminium alloy sheet under different heat treatment conditions. (November 2019) - Choi, Yumi; Moon, Chanmi; Lee, Myoug-Gyu
Abstract: Automotive bodies with high strength aluminium alloys have drawn increasing attentions due to their higher strength and lightweight capability. As one of high strength series of aluminum alloys, peak aged 7xxx series aluminum alloys exhibit superior strength of ∼ 600MPa to the conventional lower or moderate strength alloys. However, in spite of the high strength, the lower ductility has been a technical hurdle to be overcome for the material to be applied to press parts at room temperature, which leads to the development of forming technologies at elevated temperature, or namely hot forming. As an alternative to the hot forming, forming trial at room temperature has been made by performing prior solution heat treatment and quenching. This coupled heat treatment and cold forming increases the formability, while the strength needs to be recovered by additional post treatment. The treatment after forming (or deformation) includes natural aging and paint baking process inducing the artificial aging. The objective of the present study is to experimentally investigate the mechanical properties after different heat treatment conditions, which will be utilized for the future finite element simulations for the investigated forming technology.